2004
DOI: 10.1161/01.cir.0000147185.31974.be
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory G Protein Overexpression Provides Physiologically Relevant Heart Rate Control in Persistent Atrial Fibrillation

Abstract: Background-The need for new treatment strategies for cardiac arrhythmias has motivated our continuing development of gene therapeutic options. Previously, we reported a decreased heart rate in an acute model of atrial fibrillation after atrioventricular nodal gene transfer. Here, we expand those observations to persistent atrial fibrillation and severe heart failure. Methods and Results-After 3 weeks of atrial fibrillation, domestic swine received atrioventricular nodal gene transfer with adenoviruses encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 23 publications
(16 reference statements)
3
56
0
1
Order By: Relevance
“…In the study, they also showed the results of a Gai2 gene transfer were more effective than conventional ratelowering drugs such as digoxin, diltiazem, and esmolol. 46 Since the activation of AV nodal cells is regulated by Ca currents, suppression of the L-type calcium current (I ca L) in the AV node is an alternative way to reduce the ventricular response. To reduce the expression of calcium channels, Murata et al focused on a GTP-binding protein, Gem, which inhibits the trafficking of the calcium channel a subunit to the plasma membrane.…”
Section: Rate Controlmentioning
confidence: 99%
“…In the study, they also showed the results of a Gai2 gene transfer were more effective than conventional ratelowering drugs such as digoxin, diltiazem, and esmolol. 46 Since the activation of AV nodal cells is regulated by Ca currents, suppression of the L-type calcium current (I ca L) in the AV node is an alternative way to reduce the ventricular response. To reduce the expression of calcium channels, Murata et al focused on a GTP-binding protein, Gem, which inhibits the trafficking of the calcium channel a subunit to the plasma membrane.…”
Section: Rate Controlmentioning
confidence: 99%
“…32 Another study of electrophysiological modulation associated with the b-adrenergic system is gene transfer of inhibitory G protein. Donahue et al 76,77 injected adenovirus encoding inhibitory G protein a-subunit into the atrio-ventricular nodal branch and showed suppressed atrio-ventricular node conduction in their pig model of atrial fibrillation.…”
Section: Angiogenesismentioning
confidence: 99%
“…KCNH2-G628S successfully delayed the onset of atrial fibrillation. 85 Recently, Bauer et al 77 reported intra-atrial delivery of three different genes employing epicardial electroporation: dominant-negative canine ether-a-go-go-related gene channel mutant CERG-G627S, 86 small interfering RNA caspase3 (ref. 87) and connexin 43.…”
Section: Targeting Electric Dysfunctionmentioning
confidence: 99%
“…Their limited application to arrhythmia research to date (1) has resulted in biological pacemakers for treating bradyarrhythmias [26][27][28][29][30][31][32][33][34][35][36]; (2) has in part relied on global delivery of viral constructs for treating VT or AF [37,38]; and (3) for AF has also highlighted interventions that functionally or structurally ablate the atrioventricular (AV) junction [39][40][41]. There presently is need for considerable information about applicability of gene and cell therapies to specific arrhythmias, extent and duration of efficacy, safety, means for delivery, and comparison with standard device and drug therapies.…”
Section: The Status Of Antiarrhythmic Gene and Cell Therapiesmentioning
confidence: 99%
“…Here, G-alpha i2 overexpression in the porcine atrioventricular node has been achieved via injection into the atrioventricular nodal artery. The intent was to suppress basal adenylyl cyclase activity and via amplified vagal tone to indirectly reduce Ca current in the atrioventricular node [39,45]. During sinus rhythm atrioventricular conduction slowing and ERP prolongation were reported and-in the setting of atrial fibrillation-there was a 20% reduction in ventricular rate [39,45].…”
Section: Therapy Of Tachyarrhythmiasmentioning
confidence: 99%